LGG-23. Cardiac function in children and young adults treated with MEK inhibitors: a single institution retrospecive cohort study. (3rd June 2022) - Robison, Nathan; Su, Jennifer; Fang, Melody; Malvar, Jemily; Menteer, Jondavid
Abstract: INTRODUCTION: MEK inhibitors (MEKi) have shown efficacy in pediatric low-grade glioma, among other tumors, but have been associated with acute cardiac dysfunction in adults. Cardiac consequences in children are unknown. MATERIAL AND METHODS: We performed a single center retrospective cohort study evaluating cardiac function by echocardiography (echo) in children and young adults <21 years old receiving MEKi at Children's Hospital Los Angeles between October 2013 and May 2018. Blinded assessment of left ventricular function by fractional shortening (FS) and ejection fraction (EF) was performed on all available echocardiograms obtained before, during, and following therapy, as well as after re-initiation of therapy. RESULTS: Twenty-six patients underwent MEKi therapy with echo follow-up during the study period. Twenty-four of these had complete echo data. Median follow-up was 12 months. Borderline EF (EF 53-57.9%) occurred in 12 (50%) patients; and 3 (12.5%) progressed to abnormal EF (EF <53%). Cardiac dysfunction, when it occurred, was mild (lowest documented EF was 45%, and lowest FS was 24.4%). EF abnormalities typically fluctuated during therapy, resolved off therapy, and recurred with MEKi re-initiation. No clinical or demographic differences were detected between those who maintained normal cardiac function and those who developed borderline or overt cardiac dysfunction. Symptomatic heart failure did not occur. CONCLUSION: In this cohort of children and young adults, MEKi use was associated with a relatively high incidence of borderline decrease in left ventricular function, often of uncertain clinical significance. There was no evidence of permanent cardiac dysfunction. Further evaluation in larger prospective trials is needed.